Thermoluminescence studies of CaSO4:Dy, P, Si phosphor under X-ray irradiation. Issue 3 (15th February 2018) - Nair, Resmi G.; Madhukumar, K.; Nair, C.M.K.; Jayasudha, S.; Anandakumar, V.M.; Elias, T.S.; Komath, Manoj
Abstract: Results of thermoluminescence studies on CaSO4 :Dy, P phosphor with Si co-doping under X-ray irradiation are presented here. The peak emission temperature of the phosphor is found to be at 360 °C without any compromise in the intensity of emission when compared to commercially available standard phosphor CaSO4 :Dy. The fading rate of the phosphor is around 2% over a period of 90 days.